Emerging directions in public sector management in New South Wales - Kruk, Robyn; Bastaja, Annette (2002)
This article describes some of the changes taking place within NSW public sector to enable it to meet efficiently the future demands of a diverse community. It features a range of major reforms that are under way across legislative, administrative and financial frameworks to enhance the sector's ability to cope with technological advances and enhance service delivery. - Reproduced.
Keywords: Public administration